ChemInform Abstract: ZrSe3‐Type Variant of TiS3: Structure and Thermoelectric Properties. Issue 50 (16th December 2014) - Guilmeau, Emmanuel; Berthebaud, David; Misse, Patrick R. N.; Hebert, Sylvie; Lebedev, Oleg I.; Chateigner, Daniel; Martin, Christine; Maignan, Antoine
Abstract A dense TiS3 sample is prepared by solid state reaction of a 1:4 mixture of Ti and S (evacuated quartz ampoule, 600 °C) followed by spark plasma sintering in vacuum and subsequent hot press molding (600 °C, 50 MPa, 10 min).